Underwater bubble escape volume measurement based on passive acoustic under noise factors: Simulation and experimental research. (15th February 2023) - Zhang, Yu; Yu, Yao; Rui, Xiaobo; Feng, Zhu; Zhang, Jin; Chen, Yong; Qi, Lei; Chen, Xi; Zhou, Xueqian
Highlights: Simulation for clarifying the generation mechanism of bubble acoustic signal. Adaptive characteristic frequency extraction and measurement of continuous bubble volume were realized accurately. Verification of the adaptivity of various leakage rates and ambient noise. Experiment in lake water with simulated ocean noise added. Abstract: Passive acoustic methods are suitable for long-term seabed gas leak monitoring with high accuracy under the condition of low cost and simple experimental equipment. However, the impact of noise in complex underwater environments poses great challenges for measurements. In this paper, aiming at the quantitative detection problem, a theoretical model of the bubble generation process by underwater gas escape is established, and the mechanism of bubble acoustic signal generation is clarified. The model identification of bubble volume oscillation is realized through the complementary ensemble empirical mode decomposition (CEEMD) method. Then continuous bubbles are segmented by the normalized energy method to achieve a high-precision measurement of volume inversion. A measurement prototype is developed and tested in the lake with multiple noises caused by seawater disturbance, sea wind, and ships. The results showed that the measurement errors could be kept within 10% even under the condition of strong noise interference.